The Role of Gender Stereotypes, Sexual Myths, and Professional Experience on the Attitudes Toward Female-Perpetrated Sexual Abuse Among Turkish Professionals - Akdemir, Seda (International journal of offender therapy and comparative criminology, 2024)
Studies indicated that people tend to consider female-perpetrated sexual abuse (FPSA) less serious and damaging than male-perpetrated abuse (MPSA) and the possible roles of gender stereotypes on attitudes to minimize FPSA. This study aimed to explore the role of gender stereotypes and sexuality myths on the attitudes toward FPSA among professionals. A secondary aim was to explore the role of training and experience with child sexual abuse (CSA) cases on the attitudes toward FPSA. The sample consisted of Turkish professionals (N = 502), including mental health/social, health, and justice workers. The participants were recruited via a face-to-face online survey. The results of one-way ANOVAs showed that females and mental health/social workers were more likely to consider FPSA as a serious problem and believe the negative impact of abuse. A five-step hierarchical multiple regression analysis demonstrated that the experience with FPSA cases, belief in gender stereotypes, and myths about female sexuality accounted for 21.7% of the variance in the attitudes toward FPSA. Although the level of professional minimization of FPSA is above average, the influential roles of gender stereotypes and sexual myths on the attitudes toward FPSA exist among professionals. Our findings supported the necessity of additional training addressing gender stereotypes and sexual myths. Future studies should also be conducted with different populations and other influential possible factors on the attitudes toward FPSA.